Is domestic inquiry necessary before an employee is dismissed? / Suria Fadhillah Md Pauzi and Nadia Omar - Md Pauzi, Suria Fadhillah; Omar, Nadia (2004)
It is an established fact that when an employee accepts employment from an employer, he also agrees to be subjected to the authority of the employer and the discipline to the employer's undertaking. In other words, if the employee commits an act that is contrary to the system of rules in the organization, he is said to have committed an offence or misconduct and liable to be punished. Under the Employment Act 1955, an employee can only be dismissed after due inquiry (domestic inquiry). The requirement of a domestic inquiry has acquired great significance in our industrial law and towards this end it has now become a statutory requirement prior to the inflicting of punishment for misconduct as laid down under Section 14 of the Employment Act 1955. The effect of this provision is that before an employer could dismiss or downgrade the employee or suspend the employee from work for a certain period, the employer must hold a fair and proper domestic inquiry. This is to ensure that his rights as laid down by law, i.e.: - natural justice has been served. However it should be noted that when discussing this issue, a number of questions may arise, such as; Does Section 14(1) of the Employment Act 1955 make a domestic inquiry mandatory? What would be the position of an employee outside the ambit of the Employment Act 1955? What are the consequences of not holding a proper inquiry? This paper will try to answer these issues.